Field notes contributed by Hank Zaletel, spring 1996 - Zaletel, Hanket al (1996)
Spring report of birds found in central Iowa contributed by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed